Confirmation of Bevacizumab Activity, and Maintenance of Efficacy in Retreatment After Subsequent Relapse, in Pediatric Low-grade Glioma. Issue 6 (August 2015) - Kalra, Manas; Heath, John A.; Kellie, Stewart J.; Dalla Pozza, Luciano; Stevens, Michael M.; Swamy, Shruti; McCowage, Geoffrey B.
<x xml:space="preserve">Abstract</x> Background: Management of low-grade gliomas (LGG) can be a challenge, particularly when not resectable and refractory or recurrent following standard treatments. We undertook a retrospective analysis of 2 institutions' experiences treating children for refractory or progressive LGG with bevacizumab-based therapy (BBT). Procedure: Inclusion criteria were patients younger than 18 years of age who had previously failed one or more lines of therapy. Treatment was intravenous bevacizumab 10 mg/kg and intravenous irinotecan 125 to 150 mg/m2 every 2 weeks. Results: Sixteen children (median age of 8.6 y), 5 with neurofibromatosis type 1 and 8 with disseminated disease were treated between 2009 and 2013. Median duration of treatment was 12 months (range, 3 to 45 mo). Seven patients (44%) showed clinical improvement (3 patients within a month) and 8 patients (50%) remained clinically stable during BBT. Imaging studies showed 3 (19%) had a partial response, 11 (69%) stable disease, and 2 (12%) had progressive disease. Four patients had progressive disease after stopping BBT (median duration of 5 mo). Three of these 4 were able to be retreated with BBT and all achieved an objective response. Treatment was well tolerated with no grade 3 or 4 toxicities related to bevacizumab. Irinotecan was discontinued in 4 patients because of grade 2-3 toxicities. Conclusions: We conclude that BBT is well tolerated and led to disease control in patients with refractory or recurrent cases of LGG. Retreatment with BBT led to disease control in most of these cases. Larger, prospective studies are warranted to confirm these results.